PUBLIC SERVICE COMMUNICATION OF MANPOWER AND TRANSMIGRATION SERVICE IN SERVING THE PRODUCTION OF SEARCHERS' ID CARDS WORK (AK 1) IN SIKKA DISTRICT - Kriswinda Adventuriani Kalore; Markus Kristian Retu; Intan Mustafa (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The issuance of Job Seeker Card (AK 1) is one of the services provided by the Manpower and Transmigration Office (Disnakertrans) of Sikka Regency to help residents who are looking for work. This study aims to analyze public service communication implemented by Disnakertrans in the process of making AK 1. The research method used is a qualitative approach with in-depth interview techniques and participatory observation. The results of the study indicate that communication between officers and job seekers still faces obstacles in terms of clarity of information and procedures. However, most job seekers are satisfied with the responsiveness and friendly attitude of the officers. The conclusion of this study is that improving clearer and more efficient communication will improve the quality of public services at Disnakertrans of Sikka Regency. This study provides important implications related to the management of public service communication in the context of local government.